Social Anxiety in the Homosexual Community: Case Study in Kediri - Jainudin; Nisak, Agil Qiro’atun (International Conference on Sustainable Health Promotion, 2023)
Homosexuality is a deviation of social behavior which is said to be like the same sex. Homosexuals are divided into two, namely gays and lesbians. The discussed homosexuals focus on gays only. Gay is when a man likes another man. Many events and experiences have occurred that have been passed by homosexuals or gays. Social anxiety is one of the things experienced by this community. This research aims to find out the description, factors and ways to overcome social anxiety in the homosexual (gay) community in Kediri. This research was conducted using a qualitative method with a case study approach. Data collection uses in-depth interviews and how to determine the validity of the data using source triangulation. Three subjects who were interviewed with the criteria of being male, belonging to one part of the homosexual/gay community, data analysis used reduction, display and data conclusion. The results of the description of the anxiety experienced by homosexuals (gay) are physical changes marked by a racing heart, cold sweat, cold hands and trembling. there are behavioral symptoms such as speaking sluggishly and avoiding when meeting people you know and cognitive symptoms occur, namely difficulty focusing, loss of focus, lack of confidence, difficulty receiving information, feeling inferior or feeling inferior and afraid of being judged badly by others. Factors causing social anxiety are increased fear and the trauma experienced. Furthermore, to overcome social anxiety by doing relaxation such as taking deep breaths, praying and silence to then avoid and with efforts from oneself to get out of the situation that is being experienced.